Social Wellbeing in the Workplace: HR Activities and Impact - Tabor-Błażewicz, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The aim of the article is to present the results of research on social wellbeing in the workplace, with particular emphasis on the activities and social impact of Human Resources departments. Research Design & Methods: Qualitative research was carried out in the form of in-depth interviews using the author’s interview questionnaire. The target group consisted of representatives of personnel departments. Findings: The actions that companies take to influence the social wellbeing of employees as well as the measurements that companies use to evaluate their activities and wellbeing have been listed. The impact of the COVID-19 pandemic on the idea of wellbeing in companies is discussed. Companies’ plans for the future in the field of social wellbeing are presented. Implications / Recommendations: Respondents have different understandings of the definition of employees’ social wellbeing. They take many actions in the field of social wellbeing, which means that it is significant for them. HR departments are the biggest contributors to wellbeing activities, but management and the management board should also be involved. There are problems with accurate measurement of wellbeing and the effect of wellbeing activities. The COVID-19 pandemic has increased the importance of wellbeing. Contribution: Filling a gap in the research on the social wellbeing of employees in the specific circumstances caused by the pandemic and the introduction of remote work. Filling a gap regarding the evaluation of wellbeing activities carried out in organisations.